Evaluation of upper tropospheric geopotential height anomalies over the tropical and subtropical oceans in CMIP6 models using GNSS radio occultation observations - J-L F Li; Kuan-Man Xu; Wei-Liang Lee; J H Jiang; Graeme Stephens; Jia-Yuh Yu; Gregory V Cesana; Maxwell Kelley (Environmental Research Communications)
We investigate the influence of hydrometeor radiative effects on the winter (DJF) geopotential height anomaly (ZA) over the subtropical and tropical Pacific Oceans in both the Coupled Model Intercomparison Project phase 5 (CMIP5) and phase 6 (CMIP6) models, utilizing satellite observations from GPS radio occultation (RO). This study evaluates average ZA biases in historical climate simulations, focusing on the influence of how models calculate the radiative properties of frozen hydrometeors (cloud ice and falling ice). CMIP6 models are categorized based on their treatments of these radiative properties: separately (SON2), combined (SON1) and cloud ice only (NOS). NOS models exhibit overestimation of absolute ZA biases in the upper troposphere. In contrast, SON2 models reduce these biases by 30–80 m, while SON1 models show no such improvement compared to NOS. In fact, the spatially averaged ZA biases in SON1 are comparable to or larger than those in NOS, suggesting that the combined radiative effects of cloud ice and falling ice hydrometeors do not have the same impact as the separate treatment in SON2. These biases in CMIP6 also align with sensitivity tests conducted using CESM1-CAM5 and CESM2-CAM6, where turning off radiative effects of falling ice results in significantly larger ZA biases compared to simulations with these effects included. Overall, the progress from CMIP5 to CMIP6 remains somewhat limited, with improvements seen only in SON2 models. These findings suggest that independently treating cloud ice and falling ice radiative properties may be crucial for reducing variability among CMIP6 models and improving model accuracy.